2019
DOI: 10.1002/bdr2.1568
|View full text |Cite
|
Sign up to set email alerts
|

Gestational exposure to nicotine and/or benzo[a]pyrene causes long‐lasting neurobehavioral consequences

Abstract: Tobacco smoke is a complex mixture that includes thousands of compounds. Previously, we have found that gestational exposure to the complex mixture of tobacco smoke extract caused long‐term neurobehavioral impairments. In this study, we examined the interaction of two of the most biologically active, nicotine and benzo[a]pyrene (BaP). Developmental effects were determined in Sprague–Dawley rats prenatally exposed to low doses of BaP and nicotine (0.03 mg/kg/day of BaP and 2 mg/kg/day of nicotine) via maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Previous animal studies have demonstrated neuroinflammatory changes, ventriculomegaly, and increased repetitive behaviors in mice exposed with fine and ultrafine particulate matter 40‐42 . Gestational exposure to PAH and its constituents exhibited decreased learning and responses in zebra fish, and hyperactivity and reductions in fear response among rats 43,44 . Furthermore, altered cerebellar development in metabolomic and myelination patterns after perinatal particulate matter and benzo(a)pyrene exposure were also observed as possible mechanism of cerebellar neuropathy 45,46 …”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Previous animal studies have demonstrated neuroinflammatory changes, ventriculomegaly, and increased repetitive behaviors in mice exposed with fine and ultrafine particulate matter 40‐42 . Gestational exposure to PAH and its constituents exhibited decreased learning and responses in zebra fish, and hyperactivity and reductions in fear response among rats 43,44 . Furthermore, altered cerebellar development in metabolomic and myelination patterns after perinatal particulate matter and benzo(a)pyrene exposure were also observed as possible mechanism of cerebellar neuropathy 45,46 …”
Section: Discussionmentioning
confidence: 95%
“…Cumulating toxicological evidences reported neurotoxicity for major incense burning emissions, such as PM and PAH, which provided possible pathophysiological mechanism for the adverse health effects of incense burning exposure. [40][41][42][43][44][45][46] and ultrafine particulate matter. [40][41][42] Gestational exposure to PAH and its constituents exhibited decreased learning and responses in zebra fish, and hyperactivity and reductions in fear response among rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that maternal nicotine exposure (MNE) is associated with a series of adverse pregnancy outcomes, such as spontaneous abortion, preterm birth, stillbirth, fetal growth restriction, low birth weight, and sudden infant death syndrome 15 . MNE can also cause fetal behavior and learning deficits after birth, 16 and this impairment persists into adulthood 17 . Moreover, MNE enhances the susceptibility of adult offspring to chronic metabolic diseases such as metabolic syndrome, 18 lipid metabolism disorder, 19 and steatosis 20 .…”
Section: Introductionmentioning
confidence: 99%